Escolhas enunciativas e efeitos de sentidos em textos de Mariana Kalil, coluna "Por aí" de ZH - Giacomolli, Giana (2015)
In this paper we propose to understand texts expository constitution in chapter Por Aí , from Mariana Kalil, chartered on Sundays along with Donna section from Zero Hora newspaper. In her texts, Kalil uses different resources of verbal and no verbal languages, giving to the enunciations a certain identity that differ them from publications of other columnists from the section. In this context, the main objectives of this study are: a) analyze expository choices made by the author and identify the senses effects produced by such choices; b) point out recurrent expository resources that give identity to Kalil s texts and allow to recognize them by means of its invariants. To do so, it was taken as basis presupposition of expository theory over the greimasian semi optics perspective, having as main theoretical contribution the studies of Diana Barros (1997, 2012), José Luiz Fiorin (1995, 1997, 2008), Lúcia Teixeira (2004) and Regina Gomes (2009). As analysis corpus two texts from Por Aí chapter were randomly chosen, broadcasted on different dates. The analysis has showed that expository choices projected on texts produce approaching effects among enunciator and enunciatee, projecting an atmosphere of friendship, complicity and identity between both (author-reader), as there was an intimate relation between them. Such effects are due, mainly, to the projection of people categories (me-you), to the informal language used and non verbal resources applied in the texts. Besides that, expository choices constitute invariant elements in both assessed texts, either concerning verbal strategies (person, time, vocabulary choices and direct speech categories) or concerning non verbal resources (actors characters, pictures of speech, underlines between text columns, title featured with green-lemon colors). Such occurrences foist a tone and a way of being , that is, a proper identity to Kalil s texts, allowing recognize them with an enunciated enunciation, with strong presence of visual resources, on humorous and relaxed tone with tendency to exaggeration -, directed to a modern and cool female public